2023
DOI: 10.1097/ju.0000000000002956
|View full text |Cite
|
Sign up to set email alerts
|

Gleason Grade 1 Prostate Cancer Volume at Biopsy Is Associated With Upgrading but Not Adverse Pathology or Recurrence After Radical Prostatectomy: Results From a Large Institutional Cohort

Abstract: Purpose: Clinical guidelines suggest that for low-grade, clinically localized prostate cancer, patients with higher volume of disease at diagnosis may benefit from definitive therapy, although the data remain unclear. Our objective was to determine associations between low-grade prostate cancer volume and outcomes in men managed with primary radical prostatectomy. Materials and Methods: Men with cT1-2N0/xM0/x prostate cancer, prostate specific antigen at diagnosis <10 ng/mL, and Gleason grade group 1 pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Gabriel C. Dos Anjos, 1 To the Editor: We read with great interest the article by Shee et al, reporting on the oncologic outcomes of radical prostatectomy in men with Gleason Grade Group (GGG) 1 prostate cancer (PCa), which was published recently in The Journal of Urology Ò . 1 First of all, we would like to congratulate the authors for their effort in rigorously collecting and presenting very important data that will help to refine and expand patient eligibility for active surveillance (AS). AS is the way to go for all low-risk PCa patients, and the authors have demonstrated this brilliantly.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Gabriel C. Dos Anjos, 1 To the Editor: We read with great interest the article by Shee et al, reporting on the oncologic outcomes of radical prostatectomy in men with Gleason Grade Group (GGG) 1 prostate cancer (PCa), which was published recently in The Journal of Urology Ò . 1 First of all, we would like to congratulate the authors for their effort in rigorously collecting and presenting very important data that will help to refine and expand patient eligibility for active surveillance (AS). AS is the way to go for all low-risk PCa patients, and the authors have demonstrated this brilliantly.…”
mentioning
confidence: 99%
“…To the Editor: Guglielmetti et al report the results of a prospective, randomized trial comparing the outcomes of open (OPN) vs laparoscopic partial nephrectomy (LPN). 1 The authors report difficulty randomizing patients (LPN vs OPN) and closed the trial early (2020) without reaching the planned sample size enrollment. A total of 208 patients were randomized, and 84 LPNs and 96 OPNs were included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: We read with great interest the article by Shee et al, reporting on the oncologic outcomes of radical prostatectomy in men with Gleason Grade Group (GGG) 1 prostate cancer (PCa), which was published recently in The Journal of Urology ® . 1 First of all, we would like to congratulate the authors for their effort in rigorously collecting and presenting very important data that will help to refine and expand patient eligibility for active surveillance (AS). AS is the way to go for all low-risk PCa patients, and the authors have demonstrated this brilliantly.…”
mentioning
confidence: 99%
“…Giuliano B. Guglielmetti, 1 Jos e P. Junior, 1 Maurı ´cio Cordeiro,1 Rafael F. Coelho,1 and William C. Nahas 1 *…”
mentioning
confidence: 99%